Eficiência econômica no sistema de café orgânico: estudo de caso dos cooperados da COOPFAM - Turco, Patrícia Helena Nogueira; Esperancini, Maura Seiko Tsutsui [UNESP]; Bueno, Osmar de Carvalho [UNESP]; Caiado, Júlia; Oliveira, Marli Dias Mascarenhas (My University, 2012)
Aimed at satisfying a market niche, organic coffee production is a competitiveness-oriented system because it has less input costs and higher income. This study estimates the system’s economic efficiency, using production costs end gross income as economic input and output. This model was designed from original survey data, reported by a sample of producers in different stages of production, which enabled the development of average technical coefficients. Results show that annual gross income exceeds operating costs by 21%, pointing therefore to an economically efficient system.

O sistema de produção de café orgânico é uma alternativa que busca a competitividade, pois minimiza gastos com insumos e proporciona maiores rendas ao atender a um mercado específico. Este estudo estima a eficiência econômica do sistema, utilizando custos de produção e renda bruta como input e output econômico. Foi delineado um sistema de produção a partir de levantamento de dados, informados por uma amostra de produtores em diferentes estágios de produção, sendo elaborada uma matriz de coeficientes técnicos médios. Os resultados mostram que a receita bruta anual equivalente supera o custo anual equivalente em 21%, caracterizando um sistema economicamente eficiente.
Economic efficiency in the organic coffee system: a case study of COOPFAM’s members
Keywords: Organic coffee; Economic efficiency; Production system; Café orgânico; Eficiência econômica; Sistema de produção